Vocabulary related to the sacrament of Eucharist. Fragment of the french-russian thesaurus of religious lexis (part 2) - Nadezda Zhukovskaya (Вестник Православного Свято-Тихоновского гуманитарного университета: Сериа III. Филология)
This publication contains a fragment of the French-Russian Thesaurus of Religious Lexis that covers the language of Catholicism and Orthodoxy (and, to a lesser extent, Protestantism)